NOT SIGNALIZED INTERCHANGES ANALYSIS ON EDUCATIONAL PATH-GUNTUNG ALABAN IN MARTAPURA KAB. BANJAR - Mahdi Noor Erdin; Rosehan Anwar (CERUCUK, 2017)
The condition is not signalized intersection on Jl segment. Education-Guntung Alaban currently support the occurrence of traffic congestion, because the area is the road to a place of worship (dome Teacher Education), and traditional markets. It dipengeruhi by the concentration of the number of vehicles from all directions increasingly crowded, especially rush hour.This study aims to determine the performance at signalized intersections and ITP not at the present time.The study was conducted at the location of the intersection based on the survey method Highway Capacity Manual Indonesia. Then, the data was analyzed based on the Highway Capacity Manual Indonesia with the help of Microsoft Excel.In the calculation of the performance of intersections without traffic lights (existing condition) obtained the value of DS average amounted to 0.931 where the value of DS means the index level of service (ITP) that intersection, including the level of E is the volume of traffic approaching / are at capacity, the current is not stable, sometimes stopping speed.Keywords: not signalized intersection, the degree of saturation, ITP